2006
DOI: 10.1002/lsm.20450
|View full text |Cite
|
Sign up to set email alerts
|

Improved staining method for determining the extent of thermal damage to cells

Abstract: Background and Objective: Enzyme histochemical stains of frozen sections have been used by investigators to assess thermal damage. The assessment of thermal damage to cells in lipid-rich tissues such as subcutaneous tissue and sebaceous glands can be difficult due to the quality of frozen sections of such tissues. The purpose of this study is to develop an improved method for this type of evaluation. Study Design/Materials and Methods: Thick frozen sections of thermally damaged pig and human skin were stained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Evaluation of thermal damage at the protein level required use of a modified lactate dehydrogenase (LDH) assay . As a ubiquitous Krebs‐cycle protein, LDH is an established marker for cell damage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of thermal damage at the protein level required use of a modified lactate dehydrogenase (LDH) assay . As a ubiquitous Krebs‐cycle protein, LDH is an established marker for cell damage.…”
Section: Methodsmentioning
confidence: 99%
“…Compound ® (Sakura, Japan), snap‐frozen, and stored at –80 °C. Cryo‐sected samples of 50 μm were placed on glass slides and incubated at 4 °C in a medium containing 0.1 m Veronal buffer , 1.5 ng β nicotinamide adenine dinucleotide (NADH, Sigma Aldrich, N1511), 15 mg L(+) lactic acid‐sodium salt (Sigma Aldrich, L7022) and 2.5 mg nitroblue tetrazolium chloride (NBTC, Sigma Aldrich, N6876) overnight. The extent of tissue with significant protein damage was assessed by light microscopy (Leica Application Suite, Leica Germany) measuring the distance to the blue‐stained, healthy tissue.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study identified the use of LDH in laser‐induced burns as a simplified, reliable, objective method of identifying the depth of thermal injury. This technique works through detection of the LDH enzyme via a colorimetric change of soluble nitroblue tetrazolium to an insoluble blue‐purple formazan salt precipitate, which occurs in cells that are viable at the time of collection . We sought to confirm our clinical suspicion that viable tissue was being removed during tangential excision of deep partial thickness burns using LDH in addition to H&E staining as a first step towards understanding the potential regenerative capacity of deep partial thickness and full thickness burns.…”
Section: Introductionmentioning
confidence: 99%
“…This technique works through detection of the LDH enzyme via a colorimetric change of soluble nitroblue tetrazolium to an insoluble blue-purple formazan salt precipitate, which occurs in cells that are viable at the time of collection. 12 We sought to confirm our clinical suspicion that viable tissue was being removed during tangential excision of deep partial thickness burns using LDH in addition to H&E staining as a first step towards understanding the potential regenerative capacity of deep partial thickness and full thickness burns. In this study, we hypothesized that for both expert and novice clinicians, H&E staining of formalin-fixed burn tissue as a method for identifying viability of tissue is inconsistent as compared with LDH activity assessment on frozen tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Gibson discusses in her introduction that there is no agreement on the technique for assessing burn depth and in the literature, there are several approaches to histological assessment that have included observations, such as the demarcation of normal/denatured collagen, inflammation and vascular patency vs vascular congestion with changes in the endothelial cell lining . Unlike the H&E stain, LDH staining highlights viable tissue, as the enzyme is present in all living cells . This assessment of viability is important because viability, in the presence of vascular patency, indicates regenerative potential.…”
mentioning
confidence: 99%